PENGARUH LATIHAN DRIBBLING DENGAN POLA ‘SLALOM’ TERHADAP KETERAMPILAN DRIBBLING TIM BASKET PUTRI SMA NEGERI 4 PEKANBARU - Helmi Susanto; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research this is to know the effect of the dribbling the with the slalom the skills dribbling the basketball team's women SMA NEGERI 4 Pekanbaru. The purpose of this research is to find out if there is the effect of the dribbling the pattern slalom of skills dribbling the teams basketball womens SMA NEGERI 4 Pekanbaru. The data obtained as a result of the research is the quantity of data through tests before and after give you the exercise dribbling with a slalom. Data being taken through the test and measurement of 12 the teams basketball womens SMA NEGERI 4 Pekanbaru. Variabel-variabel of the research, which is a dribbling the with the slalom that is symbolized by X as variables are free, while the skills dribbling the decision is symbolized by the Y as variables are tied. Based on observation that researchers did with his coach in the teams basketball womens SMA NEGERI 4 Pekanbaru, researchers are looking and watching when athletes training or competing athletes a lot of athletes who often fail in through the obstacles of every opponent, the lack of ability to outwit your opponent with a specific moves like crossever and changes the dribbling the quickly without losing balance of the body when passing through to score. So researchers provide test skill dribble to determine the ability of dribbling the teams basketball womens SMA NEGERI 4 Pekanbaru.Analisis be done by using at, based on data analysis and discussion, it can be concluded that there is influence signifkan of dribbling the with the slalom to the skills dribbling the teams basketball womens SMA NEGERI 4 Pekanbaru, it is evident with Thitung of 6, 75 and Ttabel 1,782 the first α = 0, 05.Key Words: Dribbling the, dribbling the with the slalom.